Studies on the production of Glucose Oxidase by Aspergillus Terreus UniMAP AA-1 - Ahmad Anas Bin Nagoor Gunny (School of Bioprocess Engineering, 2011)
This research is focused on the isolation of GOx-producing indigenous fungal strain from the selected Perlis area.There are many approaches to improve the production of GOx. One of the approaches is via optimization of growth conditions. The enzymatic studies on the crude GOx produced from the isolated fungal strain are performed.